Perancangan Single Sign On Dengan Smart Card Menggunakan Active Directory Pada Politeknik Caltex Riau - Cristin; Rahmat Suhatman (Politeknik Caltex Riau, 2021)
The use of information technology has become a necessity to support the smooth process of work and learning, one of which is at the Caltex Riau Polytechnic (PCR). PCR has various systems and websites that can be used by users. In general, these systems and websites are developed by different developers and have their own login authentication system. Single sign on is an authentication system for users that with just one login the user can access several websites without having to log back into other websites. Smart cards are used as a means of easy login for users. In this study, designing and implementing single sign on authentication with a smart card using the samba active directory. Based on the results of functionality testing, the average user success in logging in windows, wordpress and email in single sign on using a smart card is 100%. Based on the results of performance tests that have been carried out, the average server CPU usage is 35% and server memory usage is 22% in the 5 user tests. Client login requests and user authentication processes affect CPU usage. While the percentage of memory usage is stable because there is no user activity that burdened memory.